Najamuddin Al-Ṭūfīy dan Konsep MaṢlaḤat - Khalik, Subehan (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2016)
For al-Ṭūfīy, maṣlaḥat is a central objective laws revealed to His servant. Benefit is a power of the human mind to beat the heat and the strength of the consensus that multiple interpretations. Al-Ṭūfīy considers reasonable force to achieve the highest place than hot (khabar aḥad) were not qaṭ'iy. Neither the ijma' that in view of al- Ṭūfīy very difficult to create. Beneficiaries according to al-Ṭūfīy able to replace the authenticity of heat and ijma 'in case of doubt to both. However, thinking about the benefits of al-Ṭūfīy has made the haters menggelarinya with various titles such as al-mulhid, al-fisk, and so on. This title is purely due to their hatred of al-Ṭūfīy. In addition, it also causes their hatred then never quoting al-Ṭūfīy intact.